THEORETICAL STUDIES OF BUSINESS PARTNERSHIP FORMS OF BUSINESS ENTITIES (Development Service Industry Management, 2024)
Forms of business partnership of economic entities, namely: organizational and legal forms of management of corporate enterprises, collective ownership enterprises, vertically integrated structures; contractual regulation of cooperation between business entities; project business partnership were studied in the article. In particular, the analysis of the legal sphere of regulation of the activities of corporate enterprises gave the authors the opportunity to conclude that such business entities are determined by stable connections, they are a single property complexes. The article states that the application of the term "business partnership" to a corporate enterprise is incorrect, since the basis of a business partnership should be the interaction (cooperation) of two or more independent counterparties to achieve a common goal.After that, the peculiarities of the functioning of vertically integrated structures were investigated. The article defines that the vertically integrated structures involves the creation of higher management bodies with the transfer to a greater or lesser extent of powers (depending on the organizational and legal form) of centralized regulation of the participants' activities. In general, they are stable integrations aimed at achieving common strategic goals and involve a partial loss of autonomy. The authors indicate that in case of changes in the interests of the participating companies, this form of cooperation becomes burdensome.Further, the article considered the relationship between business entities on a contractual basis. Such forms of partnership are defined as quite flexible. However, taking into account that the main purpose of contractual inter-firm relations is profit, it was noted that any interest of the counterparties is secondary to this aspect. The authors draw attention to the commercial basis of cooperation of such relationships. Contractual relations of business entities are usually aimed at clearly fulfilling the tasks of counterparties without an emphasis on common goals. Accordingly, the lack of common interest can lead to differences in the understanding of tasks and strategies. In addition, it is difficult to guarantee the mutual exchange of ideas and knowledge in the case of cooperation on a contractual basis.The most flexible and adaptive, according to the authors, are temporary forms of cooperation created for the implementation of a joint business project. The authors define project business partnership as "a form of cooperation between business structures or organizations to achieve a common goal or implement a specific task by pooling resources, efforts, experience and proportional distribution of risks and rewards using project management methodology", the main effects of using this form of cooperation are given in the article.
Keywords: partnership; forms of business partnership; associations of enterprises; vertically integrated structures; project business partnership